A Systematic Review of the Immune-Regulating and Anticancer Activities of Pseudolaric Acid B - Liu, Mei-lun; Sun, Dan; Li, Tan; Chen, Hong (Frontiers in Pharmacology, 2017)
Cortex pseudolaricis, the root bark of Pseudolarix kaempferi Gord, has been used to treat tinea and other skin diseases for the antimicrobial activities in Traditional Chinese Medicine (TCM). Pseudolaric acid B (PAB) has been identified as the major component responsible for the action of Cortex pseudolaricis. Recently, PAB has been demonstrated to be used as novel treatments for cancer, immune disorders, inflammatory diseases, and immunosuppression. However, the mechanisms through which PAB exerts its properties are not understood well, and little attention in the literature has been given to review its pharmacological activities before. In this review, we performed a systematic summary of the literature with respect to the anticancer, immunosuppressive and anti-inflammatory properties of PAB and its derivatives. Currently available data suggest that PAB is a promising immunosuppressive and anti-inflammatory agent candidate and should be explored further in cancer treatment and prevention.